1985
DOI: 10.1177/106002808501900609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Pharmacy Services on Prescribing on a Cardiothoracic/Vascular Surgical Unit

Abstract: A multi-faceted approach was used to study the impact of clinical pharmacy services on the cost of drug therapy on a cardiothoracic and vascular surgical service. Physician and nursing attitudes about the usefulness and likely effect of clinical pharmacist recommendations were also assessed. A cross-sectional design with a temporal factor was used to study physician prescribing of all pharmacologic classes, and particularly of antibiotics. Measurements were taken for nine months before the institution of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In ward A, where the clinical pharmacist was actively engaged in reviewing the patients' medication profiles, the cost savings were 49% as opposed to a cost saving of 16% in ward B, where the clinical pharmacist was not involved in reviewing the patients' medication profiles. Thus the significant difference in drug cost savings (33%) can be attributed to the involvement of the clinical pharmacist and this is in keeping with the findings of other investigators (Ives et al, 1987;Cooper, 1981;Herbfendal et al, 1985). However, there are no previous reports of a team approach involving physicians and a clinical pharmacist in a psychiatric hospital.…”
Section: As Shown Insupporting
confidence: 83%
“…In ward A, where the clinical pharmacist was actively engaged in reviewing the patients' medication profiles, the cost savings were 49% as opposed to a cost saving of 16% in ward B, where the clinical pharmacist was not involved in reviewing the patients' medication profiles. Thus the significant difference in drug cost savings (33%) can be attributed to the involvement of the clinical pharmacist and this is in keeping with the findings of other investigators (Ives et al, 1987;Cooper, 1981;Herbfendal et al, 1985). However, there are no previous reports of a team approach involving physicians and a clinical pharmacist in a psychiatric hospital.…”
Section: As Shown Insupporting
confidence: 83%
“…Nine showed a statistically significant reduction in costs after or with the intervention [20,25,28,32,35,38,39,49,60]. Seven studies showed trends towards cost reduction [23,29], a statistically significant reduction only on part of their analysis [26,56], or no change [48,52,59]. In six studies, statistical analysis was not performed [31,34,42,47,53,54].…”
Section: Costsmentioning
confidence: 99%
“…These practitioners have unique skill sets in promoting the safe and effective use of medications. Evidence shows the involvement of critical care pharmacists in the care of ICU patients increases the safe use of medications and decreases costs associated with drug therapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Pharmacy services for the critically ill have evolved to help meet the demands of these ever-challenging patients.…”
mentioning
confidence: 99%